85.4k views
1 vote
Solve for p -6p+7=3(2p-3)-4(-10+4p

2 Answers

7 votes

Final answer:

To solve the equation -6p + 7 = 3(2p - 3) - 4(-10 + 4p), distribute the numbers inside the parentheses, combine like terms, and then isolate the variable p. The solution for p is 6.

Step-by-step explanation:

You asked to solve for p in the equation: -6p + 7 = 3(2p - 3) - 4(-10 + 4p). To do this, first we need to simplify the equation by distributing the numbers inside the parentheses and combining like terms:

  • -6p + 7 = 6p - 9 + 40 - 16p
  • -6p + 7 = -10p + 31

Next, we add 10p to both sides of the equation to get all the p terms on one side:

  • 4p + 7 = 31

Now, subtract 7 from both sides to isolate the 4p term:

  • 4p = 24

Finally, divide both sides by 4 to solve for p:

  • p = 6

So, the solution for p is 6.

User Anthe
by
6.0k points
0 votes

p-6p+7=3(2p-3)-4(-10+4p

We move all terms to the left:

p-6p+7-(3(2p-3)-4(-10+4p)=0

We add all the numbers together, and all the variables

p-6p-(3(2p-3)-4(4p-10)+7=0

We add all the numbers together, and all the variables

-5p-(3(2p-3)-4(4p-10)+7=0


User Murtho
by
6.2k points